Construcción de un medio de comunicación interactiva para la Carrera de Software de la Universidad Estatal de Bolívar. - Arévalo Bravo, Leyton Oswaldo (2023)
The present project was developed with the purpose of helping the Software career of the State University of Bolívar to improve its interactivity through digital communication, allowing to address the student community on time. Understanding that students and teachers need to have an official source to verify the official content of the university and also that each student and teacher who is identified can express themselves through the interactive portal and leaving aside the non- corresponding and/or false information that is Mix in social networks. The system was developed applying the XP development methodology, which ensures greater control over the project as well as a more effective and efficient implementation. Visual Studio Code was used as development environment, PHP as programming language, and view controller architecture. Finally, a light, friendly, responsive and intuitive system was obtained. The system allows the user to publish their ideas, attach files to their publications that will be approved or denied by the coordinator, in addition to being able to comment on publications of other users that belong to the Software community of the State University of Bolívar; in addition to immediate access to a section where you can see the files classified by folders such as official forms, applications, etc. Keywords: Interactive communication, agile methodology, website, file management.